(untitled) (International relations and international law Journal, 2016)
The prices for oil are falling,the Russian rouble to dollar is devaluating, that is why many economists say about repeated devaluation. Many experts foretell that repeated devaluation will be in the beginning of 2015 year and advise to exchange the saved tenges into any currency, from traditional dollars and euro down to yuans. This fear is quite clear. Only in recent month, in February of this year unexpectedly for the population there was a devaluation of national currency in Kazakhstan as a result of which the new rate of tenge in relation to dollar has grown about 143 tenges up to 185 tenges. Hearings about a coming close devaluation force second-level banks to spend operations the SWAP under the rates from 15 % up to 45 % on «overnight», that in turn increases rates on deals REPO. The national bank of Kazakhstan sells dollar for maintenance of a current rate. At the same time liquidity from the share market flows into National bank of RK. National Bank of RK has already reacted to the decision of Russia in formation of free converting rouble – the corridor on tenge-roubleis changed aside strengthenings of tenge. Now the rate of tenge in relation to dollar is stable, and if the second wave of devaluationoccurs, more likely that it will happen in the beginning of the next year. Devaluation of national currency of republic can occur, if oil quotations decreaseproceeds.